PENGARUH SUBLEMENTASI PROBIOTIK TERHADAP PAKAN UNTUK MENINGKATKAN PERTUMBUHAN DAN EFISIENSI PAKAN IKAN GURAMI (Osphronemus gouramy) - Rizky Rinaldi; Indra Suharman; Adelina Adelina (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
This research was conducted on 1 November to 27 December 2015 in the Fish Nutrition Laboratory, Fisheries and Marine Sciences Faculty, Riau University. This research aimed to determine the effect of probiotic supplementation in artificial diets on feed digestibility, feed efficiency, protein retention and growth of Osphronemus gouramy. Complete Randomized Design (CRD), was used with five treatments and three replications. The treatments were probiotic supplementation in diets with different concentration i.e : P0 (without probiotic supplementation in diets), P1 (probiotic supplementation of 5 mL/kg diets), P2 (probiotic supplementation of 10 mL/kg diets), P3 (probiotic supplementation of 15 mL/kg diets) dan P4 (probiotic supplementation of 20 mL/kg diets). Probiotic given through artificial diets with 30% of crude protein content. The results showed P3 (probiotic supplementation of 15 mL/kg diets) were the best treatment with feed digestibility of 73 %, feed efficiency of 27,45%, protein retention of 24,70%, and specific growth rate of 2,44% for Osphronemus gouramy.